Gereja Sebagai Komunitas Persahabatan - Markus Situmorang (Seri Filsafat Teologi, 2020)
Friendship is not something new in human life. It has existed since man existed in the world with others. Awareness of self and other creations encourages man to build friendship. Many philosophers and theologians have had ideas about the meaning of friendship. With friendship, our life becomes meaningful. The Scriptures also give the meaning of true friendship to human being. Therefore, friendship is a very essential thing in human life. True friendship needs to be based on love, trust, sincerity, sacrifice, kindness, and so on. Friendship itself must be born from the soul. A soul that is ready to give the best for friends. The friendships built by people are often fragile and vulnerable to break up. True friendship will not be eroded by time and distance. It will last forever when a soul is united in it. The Church is a community built by Jesus. The Church is born of friendship. Jesus gathers His friends at one Eucharistic table.